Utility of the ammonia-free Birch reduction of electron-deficient pyrroles: total synthesis of the 20s proteasome inhibitor, clasto-lactacystin beta-lactone. - Donohoe, T; Sintim, H; Sisangia, L; Ace, K; Guyo, P; Cowley, A; Harling, J (2005)
A new synthesis of the 20S proteasome inhibitor clasto-lactacystin beta-lactone is described. Our route to this important natural product involves the partial reduction of an electron deficient pyrrole as a key step. By judicious choice of enolate counterion, we were able to exert complete control over the stereoselectivity of the reduction/aldol reaction. Early attempts to complete the synthesis by using a C-4 methyl substituted pyrrole are described in full, together with our attempts to promote regioselective elimination of a tertiary alcohol. The lessons learnt from this first approach led us to develop another, and ultimately successful, route that introduced the C-4 methyl group at a late stage in the synthesis. Our successful route is then described and this contains several highly stereoselective steps including a cis-dihydroxylation and an enolate methylation. The final synthesis proceeds in just 13 steps and in 15 % overall yield making it an extremely efficient route to this valuable compound.